2006
DOI: 10.1007/s00726-006-0409-8
|View full text |Cite
|
Sign up to set email alerts
|

Free amino acid and dipeptide changes in the body fluids from Alzheimer’s disease subjects

Abstract: Our aim was to determine changes in free amino acid (FAA) and dipeptide (DP) concentrations in probable Alzheimer's disease (pAD) subjects compared with control (CT) subjects using liquid chromatography and electrospray ionization tandem mass spectrometry (LCMS2). We recruited gender- and age-matched study participants based on neurological and neuropsychological assessments. We measured FAAs and DPs in cerebrospinal fluid (CSF), plasma and urine using LCMS2 with selected reaction monitoring (SRM). Imidazole-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
193
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(210 citation statements)
references
References 59 publications
15
193
0
2
Order By: Relevance
“…The literature data on tryptophan concentrations in body fluids and brain of patients with AD are inconsistent. The majority of studies have found low tryptophan concentrations in serum (Widner et al 2000), plasma (Fekkes et al 1998) and CSF (Tohgi et al 1992) while other studies showed no alterations in tryptophan concentrations in plasma (Fonteh et al 2007) and brain (Storga et al 1996) in patients with AD. Low plasma tryptophan concentration might be also a consequence of the enhanced tryptophan degradation via the kynuramine pathway (Widner et al 2000), since a dysregulation of both serotonergic and kynuramine pathways of tryptophan metabolism have been associated with pathophysiology of AD (Ruddick et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…The literature data on tryptophan concentrations in body fluids and brain of patients with AD are inconsistent. The majority of studies have found low tryptophan concentrations in serum (Widner et al 2000), plasma (Fekkes et al 1998) and CSF (Tohgi et al 1992) while other studies showed no alterations in tryptophan concentrations in plasma (Fonteh et al 2007) and brain (Storga et al 1996) in patients with AD. Low plasma tryptophan concentration might be also a consequence of the enhanced tryptophan degradation via the kynuramine pathway (Widner et al 2000), since a dysregulation of both serotonergic and kynuramine pathways of tryptophan metabolism have been associated with pathophysiology of AD (Ruddick et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…However, one possible limitation in employing carnosine as an anti-AD drug is that brain carnosine is rapidly inactivated by the activity of three different isoforms of the carnosine degrading enzyme, carnosinase. Increased carnosinase activity has in fact been found in AD patients as well as in aging individuals [27,28] and decreased plasmatic levels of carnosine have been reported in AD patients [29].…”
Section: +mentioning
confidence: 98%
“…Interestingly compared to control subjects near 30% and 60% of the metabolic pathways altered in the CSF of MCI and AD patients respectively, were also affected in plasma samples from the same individuals showing certain correlation between biofluids [123]. Amino acid and dipeptide content correlation between CSF and plasma was also accomplished by Fonteh et al including also urine in that case [98]. CSF, plasma and urine from 8 AD patients and 8 control subjects were submitted to metabolite extraction.…”
Section: Metabolomics and Ad In Plasma And Serummentioning
confidence: 98%
“…Most of them are based on the analysis of CSF, blood or post-mortem brain tissue samples, although in a lesser extent, urine has been also examined in the search of AD biomarkers [89,98].…”
Section: Metabolomics In Admentioning
confidence: 99%
See 1 more Smart Citation